Constitutional Law During the Covid-19 Pandemic in a Juridical Perspective: Challenges and Strategies - Abdulqader, Wadhah Ghassan; Assalmani, M. N. B. Asyhar (Lex Publica, 2021)
The phenomenon of the significant development of Covid-19 is increasingly causing unrest in the community because of its impact on the community's economy. Seeing the circumstances and situations caused by the Covid-19 pandemic, in fact, the implementation of emergency law by issuing an emergency law is carried out by incorporating substances regarding the handling of the Covid-19 pandemic in a comprehensive manner. Various safeguards are carried out in each country with different policy implementations. Then addressing the problems caused, especially in the economic aspect and information related to the Covid-19 pandemic, is necessary to do this firmly. This research uses a normative juridical type of research. Normative juridical writing is library research through secondary materials. This study uses a statutory approach, a conceptual approach, and a comparative approach. Source of data as research reference using literature study. The results of the study conclude that it is necessary to adjust various regulations or laws that regulate emergencies with efficient constitutional law doctrine. In addition to the application of emergency constitutional law, legal aspects must be enforced. In this case, aspects of law formation, law application, and law enforcement in a pandemic situation can run optimally, and all elements, including the community, take part in helping to break the chain of the spread of the Covid-19 pandemic by looking at aspects health, economy, and social welfare. Abstrak Fenomena perkembangan signifikan Covid-19 ini tentunya semakin menimbulkan keresahan di masyarakat karena berdampak pada perekonomian masyarakat. Melihat keadaan dan situasi yang ditimbulkan oleh pandemi Covid-19, sebenarnya penerapan undang-undang darurat dengan mengeluarkan undang-undang darurat dilakukan dengan memasukkan substansi-substansi mengenai penanganan pandemi Covid-19 secara komprehensif. Berbagai safeguards dilakukan di setiap negara dengan implementasi kebijakan yang berbeda. Kemudian menyikapi permasalahan yang ditimbulkan, khususnya dalam aspek ekonomi dan informasi terkait pandemi Covid-19, perlu dilakukan secara tegas. Penelitian ini menggunakan jenis penelitian yuridis normatif. Penulisan yuridis normatif merupakan penelitian kepustakaan melalui bahan sekunder. Penelitian ini menggunakan pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan komparatif. Sumber data sebagai referensi penelitian menggunakan studi literatur. Hasil kajian menyimpulkan bahwa perlu penyesuaian berbagai peraturan atau undang-undang yang mengatur keadaan darurat dengan doktrin hukum tata negara yang efisien. Selain penerapan undang-undang darurat, aspek hukum harus ditegakkan dalam hal ini aspek pembentukan undang-undang, penerapan undang-undang dan penegakan hukum dalam situasi pandemi dapat berjalan secara optimal dan semua elemen termasuk masyarakat turut serta membantu memutus mata rantai penyebaran pandemi Covid-19 dengan melihat aspek kesehatan, ekonomi dan kesejahteraan sosial. Kata kunci: Hukum Tata Negara, Perspektif Yuridis, Pandemi Covid-19